IMPLEMENTASI PERENCANAAN STRATEGIK DALAM PENGEMBANGAN PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM S1 STIT AL-IHSAN BALEENDAH BANDUNG - Noviyanti; Amalia , Rosemila; Mustika, Sri; Salinan; Handayani, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the implementation of strategic planning in the development of the Islamic Education Management (MPI) undergraduate study program at STIT Al-Ihsan Baleendah, Bandung. Using a qualitative descriptive approach with data triangulation techniques (observation, in-depth interviews, and document analysis), the study reveals that strategic planning was carried out through SWOT analysis and stakeholder involvement in formulating vision and mission. The implementation stage included curriculum revision, faculty training, and quality assurance supervision. Strategic evaluation was conducted through internal audits and national accreditation mechanisms, applying the PDCA cycle. The study found that the program has succeeded in integrating strategic management principles with Islamic values, enabling the institution to remain adaptive, accountable, and spiritually grounded. This research contributes both conceptually and practically to the governance of Islamic higher education, especially for private Islamic colleges (PTKIS) that face similar institutional challenges. Keywords: Strategic Planning, Islamic Education Management, Higher Education, Quality Assurance, PTKIS